Assessment of the total aqueous stem bark extract of Sacoglottis gabonensis (Baille) Urban on the anatomo-histology of Wistar rat liver, kidneys and heart - Kousso Brigitte, Kouassi; Boua Narcisse, Gnangoran; Yao Emile, Kouadio; Mama, KonÃ©; AngouÃ© Paul, Yapo (International Journal of Pharmacology and Toxicology, 2021)
Sacoglottis gabonensis is a medicinal plant used traditionally for the treatment of Buruli ulcer in CÃ´te dâ€™Ivoire. To ensure its effect over a long period of use, assessment of the total aqueous stem bark extract of S. gabonensis (ETASg) on anatomo-histology of Wistar rat liver, kidneys and heart was evaluated. ETASg was administered to Wistar rats at doses of 3.5; 35 and 350 mg/kg/day for 90 days. The liver of rats treated with ETASg at 35 and 350 mg/kg showed color and appearance changes with whitish nodules. Furthermore, histological architecture revealed micro-vesicular steatosis. In contrast, gross examination did not showed any change color and appearance of the kidneys and heart of the rats tested at all doses of ETASg compared to those of control rats. Histological sections of the kidneys and heart of rats tested at all doses of ETASg showed normal kidney and heart cells. After stopping the administration, the liver abnormalities disappeared at the end of the 120 days. This study revealed that the integrity of the liver tissue is preserved only with ETASg of 3.5 mg/kg. On the other hand, it is guaranteed at all the doses studied for the renal and cardiac tissues.Â